Combustion, noise, vibrations and spray characterization for Karanja biodiesel fuelled engine. (5th August 2016) - Patel, Chetankumar; Agarwal, Avinash Kumar; Tiwari, Nachiketa; Lee, Sanghoon; Lee, Chang Sik; Park, Sungwook
Highlights: Investigations on a genset engine using Karanja biodiesel and blends. Increase in ambient pressure led to lower spray penetration. Biodiesel spray evolution was slower than mineral diesel. Karanja biodiesel showed higher heat release rate. KB20 showed higher combustion noise & vibrations in vertical direction. Abstract: An experimental study was carried out for assessing noise, vibrations, combustion, and spray characteristics and associated correlations using a single cylinder compression ignition engine. Such engines are typically used in genset and agricultural farm machinery. Tests were conducted from no load to full load using three different test fuels; Karanja biodiesel, 20% (v/v) Karanja biodiesel blend and baseline mineral diesel. Spray visualization experiments were conducted in a constant volume spray chamber using a mechanical fuel injector, similar to the one used in the test engine. Engine combustion noise as well as overall engine noise measurements were carried out using a microphone. Three different accelerometers were used to measure engine vibrations in pistonic, longitudinal and lateral directions. Combustion noise was found to be highest for 20% biodiesel blend was correlated to shorter combustion duration, increased ignition delay, and higher heat release rate. Vibration levels in the pistonic direction were found to be highest for KB20 fuelled engine. External engine noise measured by microphone was higher for KB100 at almost all loads compared to other test fuels. However, such a divergence was attributable to other sources of noise, which were not related to the combustion process. Finally, spray investigations for different test fuels showed maximum spray penetration for KB20, and the least for baseline mineral diesel. These observations were also consistent with other observations related to combustion noise, ignition delay, and heat release rate.